Neuroimmunity dynamics and the development of therapeutic strategies for amyotrophic lateral sclerosis - Bowerman, Melissa; Vincent, Thierry; Scamps, Frédérique; Perrin, Florence E.; Camu, William; Raoul, Cédric (Frontiers in Cellular Neuroscience, 2013)
Amyotrophic lateral sclerosis (ALS) is a fatal paralytic disorder characterized by the progressive and selective loss of both upper and lower motoneurons. The neurodegenerative process is accompanied by a sustained inflammation in the brain and spinal cord. The neuron-immune interaction, implicating resident microglia of the central nervous system and blood-derived immune cells, is highly dynamic over the course of the disease. Here, we discuss the timely controlled neuroprotective and neurotoxic cues that are provided by the immune environment of motoneurons and their potential therapeutic applications for ALS.